Design with Sound: The Relevance of Sound in VR as an Immersive Design Tool for Landscape Architecture - Luoma, Loviisa; Fricker, Pia; Schlecht, Sebastian J. (Journal of Digital Landscape Architecture, 2023)
Sound in landscape architecture commonly focuses on noise. In design or planning process sound rarely plays a holistic and essential role. This is partly due to the need for more tools to address the complex topic. This research introduces novel opportunities to explore the importance of sound as an immersive design parameter in landscape architecture and planning within Virtual Reality (VR). The project investigates immersive sound experiences by presenting sonic data in audible form. A VR app was constructed from multiple on-location spatial sound recordings. Within a test case, the application was used by participants, comparing a conventional design approach with the proposed VR methodology. The outcome of the test clearly shows the importance of integrating sound in an audible form to enhance the comprehensive understanding of space. The paper will focus on the discussion of the technical as well as the design-specific components.
CRIS-Team Scopus Importer:2023-11-06
Keywords: Immersive soundscape; Landscape Architecture Design and Planning with Sound; Spatial Sound; Virtual Reality